Pioneer girl : the annotated autobiography - Wilder, Laura Ingalls, 1867-1957; Hill, Pamela Smith (Pierre, South Dakota : South Dakota Historical Society Press, 2014)
Follows the Ingalls family's journey through Kansas, Missouri, Wisconsin, Minnesota, Iowa, back to Minnesota, and on to Dakota Territory, examining sixteen years of travels, unforgettable experiences, and the everyday people who became immortal through Wilder's fiction. Using additional manuscripts, letters, photographs, newspapers, and other sources, Wilder biographer Pamela Smith Hill adds context and leads readers through Wilder's growth as a writer.
Introduction: "Will it come to anything?": The story of Pioneer Girl / Pamela Smith Hill -- The Pioneer Girl manuscripts / Pamela Smith Hill -- Editorial procedures / Nancy Tystad Koupal & Rodger Hartley -- Pioneer Girl: Kansas and Missouri, 1869-1871 ; Wisconsin, 1871-1874 ; Minnesota, 1874-1876 ; Iowa, 1876-1877 ; Minnesota, 1877-1879 ; Dakota Territory, 1879-1880 ; Dakota Territory, the hard winter of 1880-1881 ; Dakota Territory, 1880-1885 ; Dakota Territory, 1881-1888 -- Conclusion: "I don't suppose anyone will take the trouble" / Pamela Smith Hill -- Appendixes: Facsimile of "Juvenile Pioneer Girl" ; The Benders of Kansas ; The Gordon party ; The singing school.
"A publication of the Pioneer Girl Project"
Includes bibliographical references (pages 371-379) and index.
Keywords: Wilder, Laura Ingalls, -- 1867-1957.; Women authors, American -- 20th century -- Biography; Women pioneers -- United States -- Biography; Frontier and pioneer life -- United States; Wilder, Laura Ingalls, -- 1867-1957.; Frontier and pioneer life; Women authors, American; Women pioneers; United States; 1900 - 1952; Biography; Autobiographies